2007
DOI: 10.1088/1742-6596/85/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Internal and near nozzle flow characteristics in an enlarged model of an outwards opening pintle-type gasoline injector

Abstract: The internal nozzle and near the nozzle exit flows of an enlarged transparent model of an outwards opening injector were investigated for different flow rates and needle lifts under steady state flow conditions. A high resolution CCD camera, high speed video camera and an LDV system were employed to visualize the nozzle flow and quantify the tangential velocity characteristics. The images of the internal flow between the valve seat and the square cross-section end of the needle guide revealed the presence of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…However, the results showed that up to a flow rate of 1.3 l/s the spray surface was always rough independent of valve lift. Observation of the spray in the new enlarged cavitating model showed a different structure to that observed in the non-cavitating injector [16]. A small sample of the results, presented in Figure 8, clearly show the complex nature of the spray with its many jet like strings which suggests that, apart from ambient effects on the emerging spray, there have to be changes in the flow structure within the annular nozzle passage.…”
Section: Spraymentioning
confidence: 87%
See 4 more Smart Citations
“…However, the results showed that up to a flow rate of 1.3 l/s the spray surface was always rough independent of valve lift. Observation of the spray in the new enlarged cavitating model showed a different structure to that observed in the non-cavitating injector [16]. A small sample of the results, presented in Figure 8, clearly show the complex nature of the spray with its many jet like strings which suggests that, apart from ambient effects on the emerging spray, there have to be changes in the flow structure within the annular nozzle passage.…”
Section: Spraymentioning
confidence: 87%
“…The steady flow rig, which was similar to that presented in [3,16], comprises two pumps, connected to the model injector at its inlet and outlet to provide the maximum pressure difference across the injector, a supply tank and an ultrasonic flow meter as shown in Figure 2. The large-scale model injector, made from acrylic (Perspex), is geometrically similar to the real size injector but 23.3 times larger.…”
Section: Flow Arrangement and Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations